Proton, Alpha, and Gamma Rays Interactions of CsI(Na) Scintillator Using the Theoretically Computational Program. Issue 1 (28th March 2022) - Borisut, P.; Chaiphaksa, W.; Limkitjaroenporn, P.; Insiripong, S.; Kaewkhao, J.; Sangwaranatee, N.; Sangwaranatee, N. W.
Abstract: The charged particles and photon interaction parameters of CsI(Na) scintillator were calculated by the theoretically computational program. The Phy-X programs were used to calculation gamma rays interaction at an energy range of 1 keV to 100 GeV. The stopping and range of ions in matter program were used for measurement the proton and alpha particles. The result found that the total mass attenuation coefficient decreased with the increasing of the high photon energy range and found the discontinuous energy due to the absorption edge of Cs and I. The effective atomic number and the effective electron density found the same trend with the total mass attenuation coefficient. The data of mass stopping powers for proton and alpha particle increase to the maximum value at kinetic energy 0.09, 0.6 MeV, respectively. The results showed that the energy at 5 keV, the ions entering the scintillator penetrate less deeply than the energy of the ions at 10 keV.